Long non-coding RNAs: Modulators of phenotypic transformation in vascular smooth muscle cells - Lu, Bing-Han; Liu, Hui-Bing; Guo, Shu-Xun; Zhang, Jie; Li, Dong-Xu; Chen, Zhi-Gang; Lin, Fei; Zhao, Guo-An (Frontiers in Cardiovascular Medicine, 2022)
Long non-coding RNA (lncRNAs) are longer than 200 nucleotides and cannot encode proteins but can regulate the expression of genes through epigenetic, transcriptional, and post-transcriptional modifications. The pathophysiology of smooth muscle cells can lead to many vascular diseases, and studies have shown that lncRNAs can regulate the phenotypic conversion of smooth muscle cells so that smooth muscle cells proliferate, migrate, and undergo apoptosis, thereby affecting the development and prognosis of vascular diseases. This review discusses the molecular mechanisms of lncRNA as a signal, bait, stent, guide, and other functions to regulate the phenotypic conversion of vascular smooth muscle cells, and summarizes the role of lncRNAs in regulating vascular smooth muscle cells in atherosclerosis, hypertension, aortic dissection, vascular restenosis, and aneurysms, providing new ideas for the diagnosis and treatment of vascular diseases.